Involvement of KLF11 in hepatic glucose metabolism in mice via suppressing of PEPCK-C expression. - Huabing Zhang; Qi Chen; Tao Jiao; Anfang Cui; Xiujing Sun; Weijun Fang; Liwei Xie; Yang Liu; Fude Fang; Yongsheng Chang (PLoS ONE)
Background Abnormal hepatic gluconeogenesis is related to hyperglycemia in mammals with insulin resistance. Despite the strong evidences linking Krüppel-like factor 11 (KLF11) gene mutations to development of Type 2 diabetes, the precise physiological functions of KLF11 in vivo remain largely unknown. Results In current investigation, we showed that KLF11 is involved in modulating hepatic glucose metabolism in mice. Overexpression of KLF11 in primary mouse hepatocytes could inhibit the expression of gluconeogenic genes, including phosphoenolpyruvate carboxykinase (cytosolic isoform, PEPCK-C) and peroxisome proliferator-activated receptor γ coactivator-1α (PGC-1α), subsequently decreasing the cellular glucose output. Diabetic mice with overexpression of KLF11 gene in livers significantly ameliorated hyperglycemia and glucose intolerance; in contrast, the knockdown of KLF11 expression in db/m and C57BL/6J mice livers impaired glucose tolerance. Conclusions Our data strongly indicated the involvement of KLF11 in hepatic glucose homeostasis via modulating the expression of PEPCK-C.